Social structure and rural economic development - Berger, Guy (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 1989)
New concepts and a synthesis of existing theories may assist in studying the relationship between social structure, development and rural development. The concept of social structure encompasses the concept of economic structure which may be analysed in terms of three "Moments" of production. On this basis, one can distinguish between heterogeneous and homogeneous relations of production structures. "Homogeneous relations" together with "system dynamics" and ''reproduction", define the concept of a mode of production. "Development" refers to the expansion of total productive capacity, premissed on advanced means of production, and corresponding to the particular relations and forces of production in an economic system. The capitalist mode of production has both tendencies and countertendencies to development. The latter prevail in the Third World due to the admixture and heterogeneity of production relations there, and to their subordinate articulation within an international capitalist economic system. In this context, underdevelopment is the result of the specific factors of monopoly competition, dependence-extraversion, disarticulation-unevenness, the three-tier structure of the peripheral economy, surplus transfer, and class structures and struggles. Rural development can be understood in terms of the specific contribution of agriculture to development, theorized as the "Agrarian Question". Agrarian capitalism has been slow to develop in the Third World, and the state of agriculture remains a problem there. "Rural development" has emerged as a deliberate and interventionist state strategy designed to restructure agrarian relations for development. This has contributed to the formation of particular heterogeneous relations of production articulated to the capitalist mode. In this context, the character of the associated classes has left the Agrarian Question unresolved. "Rural development" continues because it has an important~ and even primary, political significance - although this is not without contradictions.
Keywords: Social structure -- Developing countries; Rural development-- Developing countries